Validation of a Swiss method of caries prediction in Dutch children - van Palenstein Helderman WH, Mulder J, van’t Hof MA, Truin GJ (Blackwell Synergy, 2001)
This study aimed to validate a caries prediction method, the Dentoprog-Method, which was developed on Swiss children. Method: A Dutch child population was used for validation.